Knowledge and Attitudes of Maternity Nurses and Ancillary Team Members about Substance Addiction during Pregnancy and Postpartum. Issue 2 (March 2021) - Munoz, Katrina; Suchy, Carol; Rutledge, Dana N.
Abstract: Objective: To describe knowledge and attitudes of maternity nurses and other ancillary direct caregivers about addictive substance use by pregnant women and new mothers and to evaluate their perceptions of role preparation, resources available, and educational needs. Study Design & Methods: We surveyed maternity nurses and ancillary members of the maternity care team to assess knowledge and attitudes about caring for women with addictive substance use. Data were analyzed using descriptive, parametric, and nonparametric statistics. Results: Respondents ( N = 109) from a southwestern Magnet community hospital were 100% female, predominantly nurses (89%), and worked mostly on mother–baby or labor and delivery units. They had high average knowledge scores and most had positive attitudes. When asked about preparation to care for pregnant women and new mothers with addictive substance use, some perceived that they were not able to carry out their role due to lack of knowledge. Clinical Implications: Findings suggest most maternity nurses have the knowledge and skills they believe are needed to care for women who use addictive substances during pregnancy and postpartum. Most have positive attitudes, but approximately one third may need interventions to encourage and further support empathy and acceptance. Education and skill-building for maternity nurses and other team members related to caring for women using addictive substances may be worth consideration; however, there is minimal evidence of their efficacy. Evaluations of these types of programs are needed in maternity settings. Abstract : Maternity nurses and ancillary members of the maternity care team in one Magnet hospital were surveyed about their knowledge and attitudes in caring for women during pregnancy and postpartum who use addictive substances. Most maternity nurses have the knowledge and skills they believe are needed and most, but not all, have positive attitudes in caring for this vulnerable population.